Quelques cas de séparation pour adultère masculin entre xvie et xviie siècles : arguments et enjeux - Claire Chatelain; Raphaëlle Lapôtre; Camille Noûs (Genre & Histoire)
Based on case studies centered on couples' requests for separation by the judicial means of male adultery or cohabitation in the sixteenth and early seventeenth centuries, this article compares two types of competent jurisdictions for this charge, one secular and royal, the other ecclesiastical ; and two types of procedures, one accusatory and the other inquisitorial. For the former, the accusation of adultery refers to several series of failures by the husband of a sexual, generative, economic or patrimonial order but also, moral or political. In the second case, the accusation is of a formal nature and a breach of the sacramental order, to the exclusion of other considerations. The cases submitted for judicial review show , the practices of couples that did not conform to official norms.